Sifat Fisik Dan Kimia Beras Analog Berbagai Varietas Tepung Ubi Jalar Disubtitusi Dengan Tepung Jagung - Leonardo Satelit Balitar (Fakultas Pertanian, 2025)
Rice is a staple food in Indonesia but the increasing demand for rice consumption is not supported with the domestic production. Analog rice is made by granulation method. This study used the design of Randomized Block Design (RBD) with factors including varieties of sweet potato substituted with corn flour. Factors consisted of 3 levels; 70% flour of purple sweet potato (Ayamurasaki variety) and 30% corn flour, yellow sweet potato (Cilembu variety) 70% and corn flour 30%, Purple sweet potato (Ayamurasaki variety) 35%, Cilembu 35%, and corn flour 30%. The variables observed consisted of proximate test, antioxidant activity, and rehydration. The results demonstrated a significant difference in protein content and antioxidant activity. On the other hand, there were no significant differences in water content, ash, fat, carbohydrate and rehydration ability. The highest protein content (2.42%) was obtained in the treatment of 70% yellow sweet potato flour and 30% corn flour. In addition, the highest antioxidant activity of analog rice (16.01%) was obtained in the treatment of 70% purple sweet potato flour and 30% corn flour.